COMPARATIVE SEQUENCE ANALYSIS OF TLR2 TLR4 AND TLR9 GENES AMONG SELECTED VERTEBRATES-A META-ANALYSIS - Das, Avishek; Guha, Pokhraj; Chaudhuri, Tapas Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Toll-like receptors are the pattern recognition receptors that recognize a diverse set of conserved pathogens. The receptors are also constantly under selection pressure because of the host antigen modifications. The present study focuses on how selection and mutation have modified the TLRs throughout the evolution in selected groups. Methods: We have selected the sequences of TLR2, 4 and 9 among Hominid group, Homo sapiens, Bubalus bubalis and Danio rerio in our analysis and analyzed different parameters like relative synonymous codon usage (RSCU), sequence divergence, amino acid composition and estimated evolutionary selection forces using Tajima's test. Results: The phylogenetic assessment proved that positive selection influences TLR2 and TLR4, but neutral selection/balancing selection occurred in TLR9 which concluded from the Tajima's test. Synonymous codon usage described the selection of leucine and arginine in all the sequences which describe the structural similarities of TLRs. Values of nucleotide pairs and disparity index proved the close relationship of Hominid and Human between TLR2 and TLR4 and TLR9 where the distant relationship was found with Danio. It can be hypothesized that some of the codons may be best selected for binding with the antigens and it was selected in the genome and some were eliminated due to selection pressure. Conclusion: The present study aimed to substantiate the closeness of TLR2 and TLR4 due to their functional similarity but distant with TLR9 because of the different antigens they recognized in the endosome.